SEBUAH CATATAN PERJUMPAAN ADA’ MAPPURONDO, ISLAM DAN KRISTEN DALAM TRADISI PAMBAYAAN KU’BU’ DI JEMAAT SEPANG - Enni Rosa (Tepian : Jurnal Misiologi dan Komunikasi Kristen, 2021)
The author makes an encounter with 'the other' through interculturality in the Mamasa Toraja Church with the tradition of a family event which is defined as a once organized event, namely pambayaan ku'bu in the intercultural mission process. The author uses the thoughts of Theo Sundermeier's stating that intercultural theology can make a contribution to a society, where people have different backgrounds. The type of research used is library research or library research and the method used is a qualitative analysis of tradition and church. The results of research from tradition and church show that this pambayaan ku'bu 'event, the encounters and interactions that occur not only transcend religious relations, but also exceed life with attachments to departed ancestors